Resolution of a fluorosis case through the association of minimally invasive techniques - Danielle Ferreira Sobral de Souza; Josué Junior Araújo Pierote; Flávio Henrique Baggio Aguiar; Luís Alexandre Maffei Sartini Paulillo; Débora Alves Nunes Leite Lima (Universidade Estadual de Campinas, 2019)
Color changes may interfere with smile balance and they represent a clinical challenge to dentists. Dental fluorosis originates from intrinsic factors and it is a disorder of enamel formation during the phase of teeth development, resulting in the change of enamel color. This clinical case report aimed to present the resolution of a case of dental fluorosis through the association of minimally invasive techniques, namely microabrasion and tooth bleaching. A 27-year-old male patient sought the dental clinic of the School of Dentistry of Piracicaba (FOP - UNICAMP, Brazil) presenting striped and symmetrical white stains and generalized chromogenic biofilm. After anamnesis and clinical examination, the patient was diagnosed with fluorosis stains. Initially, adequacy of the oral environment was performed with prophylaxis and supragingival scraping. Then, the enamel microabrasion technique was performed with 6% hydrochloric acid associated with silicon carbide (Whiteness RM - FGM) and supervised at-home bleaching was performed with 16% carbamide peroxide (Whiteness Simple 16% - FGM). In conclusion, the treatment performed reestablished the aesthetics and harmony of smile color with minimally invasive procedures without causing tooth sensitivity.